Relevance of flow cytometric enumeration of post‐thaw leucocytes: influence of temperature during cell staining on viable cell recovery. Issue 2 (1st April 2016) - Fritsch, G.; Frank, N.; Dmytrus, J.; Frech, C.; Pichler, H.; Witt, V.; Geyeregger, R.; Scharner, D.; Trbojevic, D.; Zipperer, E.; Printz, D.; Worel, N.
Abstract : Background and Objectives: Our post‐thaw cell recovery rates differed substantially in interlaboratory comparisons of identical samples, potentially due to different temperatures during cell staining. Materials and Methods: Viable CD34 + cells and leucocyte (WBC) subtypes were quantified by multiparameter single‐platform flow cytometry in leucapheresis products collected from 30 adult lymphoma and myeloma patients, and from 10 paediatric patients. After thawing, cells were prepared for analysis within 30 min between thawing and acquisition, at either 4°C or at room temperature. Results: For cell products cryopreserved in conventional freezing medium (10% final DMSO), viable cell recovery was clearly lower after staining at 4°C than at RT. Of all WBC subtypes analysed, CD4 + T cells showed the lowest median recovery of 4% (4°C) vs. 25% (RT), followed by CD3, CD34 and CD8 cells. The recovery was highest for CD3γδ cells with 44% (4°C) vs. 71% (RT). In the 10 samples cryopreserved in synthetic freezing medium (5% final DMSO), median recovery rates were 89% for viable CD34 (both at 4°C and RT) and 79% (4°C) vs 68% (RT) for WBC. Conclusions: The post‐thaw environment and, potentially, the cryoprotectant impact the outcome of cell enumeration, and results from the analysis tube may not be representative of the cells infused into a patient.